Historical Perspectives in CSPAP: Examining One PETE Program's Story. Issue 6 (24th July 2022) - Heidorn, Brent; Mosier, Brian; Stoepker, Peter
Abstract: This article provides an in-depth review of a physical education teacher education (PETE) program and how it has in the past or continues to incorporate a comprehensive school physical activity program (CSPAP) within its curriculum and extracurricular programming. There are various ways to provide students with meaningful experiences that prepare them to gain confidence and take on the role of a physical activity leader (PAL) once they graduate. Though not all PETE programs can implement every single CSPAP-related effort identified here, it is critical to make sure that students are provided experiences outside of the traditional classroom. This will help them continue to grow and learn how to become a champion for physical education and schoolwide physical activity (PA) promotion.